Institutional climate in teaching performance in a public educational institution in Lima, Perú - Nina-Cuchillo, Josue (2024)
The institutional climate is an aspect of interest for educational institutions that seek to improve the performance of their teachers. Therefore, the purpose of the research was to determine if the institutional climate influences the performance of teachers at a public educational institution in Lima, Peru. A methodology was used under a quantitative approach, causal correlational level and non-experimental design. The census sample was made up of 85 teachers, to whom two questionnaires were applied to measure their perception. According to the findings, the institutional climate is at a low level and teaching performance has a poor level, determining that the institutional climate affects teaching performance in a direct and significant way.